1997
DOI: 10.1007/s004490050309
|View full text |Cite
|
Sign up to set email alerts
|

Pressure effects in cross-flow microfiltration of suspensions of whole bacterial cells

Abstract: The effect of Trans-Membrane Pressure (TMP) on permeate flux during cross-flow microfiltration of bacterial cell suspensions in tubular ceramic membranes is studied experimentally. Continuous filtration experiments with suspensions of whole bacterial cells (Mycobacterium M156) show a dramatic permeate flux decline with increasing TMP. During the very early stages of the filtration process, a linear relationship between permeate flux and TMP is observed, suggesting an initial surface sorption of cells on the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 38 publications
2
11
1
1
Order By: Relevance
“…1). This decrease was explained by an increased concentration in cells and cell residues, which, when deposited on the membrane surface, led to a decrease in TMP [17] due to additional resistance to the permeate flux through the membrane [4]. This behavior differed from that observed by Carrère et al [18], who reported a faster reduction of the permeate flux at the beginning of the process followed by a constant and stable value.…”
Section: Effect Of Microfiltration Conditions On Process Performancescontrasting
confidence: 72%
See 1 more Smart Citation
“…1). This decrease was explained by an increased concentration in cells and cell residues, which, when deposited on the membrane surface, led to a decrease in TMP [17] due to additional resistance to the permeate flux through the membrane [4]. This behavior differed from that observed by Carrère et al [18], who reported a faster reduction of the permeate flux at the beginning of the process followed by a constant and stable value.…”
Section: Effect Of Microfiltration Conditions On Process Performancescontrasting
confidence: 72%
“…The same behavior was previously described during microfiltration of Lactococcus lactis ssp. lactis ATCC19435 [6], Mycobacterium M156 [17] and Bacillus subtilis [19]. Finally, condition CF5 (3.25 m/s and 0.1 MPa) was characterized by an intermediate behavior.…”
Section: Effect Of Microfiltration Conditions On Process Performancesmentioning
confidence: 99%
“…According to Redkar and Davis15 and to Tanaka et al,10 the initial transient flux decline in the cross‐flow mode follows the dead‐end filtration law. Numerous yeast microfiltration experiments performed on membranes of pore size less than 1 μm confirm the cake filtration mode and the possibility of using the Carman–Kozeny equation to model the cake permeability/hydraulic resistance 4, 6–8, 21–24…”
Section: Introductionmentioning
confidence: 87%
“…Das eingesetzte Mikrofilter hat eine Porengröûe von 0,2 lm, so dass die Produkte einer Molekülgröûe von 8 und 60 kDa in das Erntegefäû gelangen können [14]. Mit der nachfolgenden Ultrafiltration bei einem cut off von wahlweise 1 bis 5 kDa wird das Produkt durch Abtrennung niedermolekularer Stoffe und Flüssigkeit aufkonzentriert [15].…”
Section: Biostream ± Eine Anbindung Der Primäraufarbeitungunclassified